Cost-effectiveness Analysis Of Idursulfase For The Treatment Of Hunter Syndrome In A Tertiary Referral Centre For Rare Diseases In Malaysia: A Partitioned Survival Model Approach - Mustaffa, Khairu Hazwan (2024)
Hunter syndrome (MPS-II) is among the costliest life-long genetic conditions associated with a substantial burden of illness and its significant impact on Malaysia's health systems, families, and society. There needs to be more studies demonstrating its value for money incorporating long-term effectiveness data, local costs situation, and population-specific utility values. The objective is to estimate the cost-effectiveness of long-term enzyme replacement therapy of idursulfase (ERTI) versus standard-of-care (SOC) from a societal using a streamlined modelling strategy in R. A de novo four states partitioned survival model approach was utilised to project and compare lifetime costs, QALYs, and incremental cost-effectiveness ratios of two care models. The disease progression was based on independent survival modelling of relevant published Kaplan-Meier (KM) data. The healthcare and out-of-pocket costs were drawn from the local setting. The quality-of-life was measured using the EQ5D5L and the TTO valuation of health state vignettes that matches the states in the model. Probabilistic and deterministic sensitivity analyses were conducted to test the uncertainty around the model results. The life expectancy was significantly longer in the ERTI than in the SOC, with SOC patients not surviving beyond the second decade of life on average. In contrast, life expectancy in the ERTI group exceeded 20 years (95% CI, 19.02-20.70). The lifetime incremental QALYs were 4.1 years (2.37-5.68).